Application in a linear proton accelerator of a non-vaporizable Zr(86)-Al(14) getter located inside the chamber of a plasma-ion proton injector for its additional pumping - Aksonova, A.M.; Belicov, V.V.; Vdovin, S.A.; Makhnenko, P.L.; Pylypenko, M.M.; Podolyak, A.P.; Ponomarchuk, E.I.; Svynarenko, O.P.; Skibin, V.I. (Вопросы атомной науки и техники, 2022)
The rates of pumping hydrogen and nitrogen by the non-evaporable Zr(86)-Al(14) getter located inside the chamber of a plasma-ion proton injector are investigated. The measurements at the temperature range 473…1300 K and pressures from 13 to 10⁻³ Pa were carried out. The highest pumping rates of hydrogen ((283±15) l/s) and nitrogen ((133±15) l/s) achieved at the temperature range 525…575 K and pressure from 13 to 10⁻³ Pa has been established. It is shown that the proposed non-evaporated getter Zr(86)-Al(14) provided the required operating pressure in the chamber of the plasma-ion injector of the linear proton accelerator and the minimum concentration of hydrogen, nitrogen, and other residual gases.